Nigeria School Health : SABER Country Report 2015 - World Bank Group (World Bank, Washington, DC, 2017)
This report presents an assessment of school health policies and institutions that affect young children in Nigeria. The analysis is based on a World Bank tool developed as part of the Systems Approach for Better Education Results (SABER) initiative that aims to systematically assess education systems against evidence based global standards and good practice to help countries reform their education systems to help ensure learning for all. School health policies acritical component of an effective education system, given that children's health impacts their school attendance, ability to learn, and overall development. SABER School Health collects, analyzes, and disseminates comprehensive information on school health policies around the world. The overall objective of the initiative is to help countries design effective policies to improve their education systems, facilitate comparative policy analysis, identify key areas to focus investment, and assisting disseminating good practice.